2004
DOI: 10.1158/0008-5472.can-03-1717
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tumorigenicity and Metastasis of Human Melanoma Cells by Anti-Cathepsin L Single Chain Variable Fragment

Abstract: We demonstrated previously that the switch from nonmetastatic to highly metastatic phenotype of human melanoma cells is directly related to secretion of procathepsin L form. This cysteine proteinase was identified on the basis of its property to cleave human C3, the third component of complement. In an attempt to control procathepsin L secretion, we have recently generated an anti-cathepsin L single chain variable fragment (ScFv) from an anti-cathepsin L monoclonal antibody generated against recombinant cathep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 25 publications
3
86
1
Order By: Relevance
“…5). These data agree well with the observations of others (35,36) who evaluated the effect of the distinct but functionally similar cathepsin L protease on the deposition of C3b on cell surfaces. Our findings show that MT1-MMP inhibits complement activation by clearing cell surface-deposited C3b and C4b from a tumor cell with the resultant release of their respective inactive soluble forms into the extracellular milieu.…”
Section: Mt1-mmp Efficiently Cleaves C3b In Both Cell-free and Cellbasupporting
confidence: 92%
See 1 more Smart Citation
“…5). These data agree well with the observations of others (35,36) who evaluated the effect of the distinct but functionally similar cathepsin L protease on the deposition of C3b on cell surfaces. Our findings show that MT1-MMP inhibits complement activation by clearing cell surface-deposited C3b and C4b from a tumor cell with the resultant release of their respective inactive soluble forms into the extracellular milieu.…”
Section: Mt1-mmp Efficiently Cleaves C3b In Both Cell-free and Cellbasupporting
confidence: 92%
“…Conversely, inhibition of the C3-cleaving cathepsin L-like cysteine proteinase p39 strongly decreased tumorigenicity and the metastatic potential of human melanoma xenografts in nude mice (17). In agreement, transfection with L-cathepsin transformed non-metastatic melanoma cells into highly tumorigenic and metastatic cells (35,36). In a similar fashion, expression of rat Crry (an inhibitor of complement activation) inhibited the in vivo deposition of complement C3 fragments and sharply enhanced the tumorigenicity of MCF7 cells.…”
Section: Mt1-mmp Does Not Affect the Expression Of The Cellularmentioning
confidence: 63%
“…18 Then, we demonstrated that in vitro stable transfection with the cytomegalovirus promoter (pCMV)/myc/ER-anti-CTSLScFv expression vector of A375SM human melanoma cells, characterized by a high tumorigenic and strong metastatic phenotype, led to: (1) intracellular expression of anti-human CTSL-ScFv; (2) strong inhibition of procathepsin L secretion by transfected cells, without modifying their intracellular amount or processing pattern of cathepsin L forms; and (3) switch their phenotype to very poorly tumorigenic and non-metastatic. 19 In vivo, cells transfected with this anti-CTSLScFv produced less and smaller tumors with a decrease of vascularization (angiogenesis) and an increase of cell apoptosis. 19 Furthermore, our recent demonstrations that overexpression of cathepsin L in human tumor cells is under the control of separate and complex regulatory mechanisms 20,21 support that procathepsin L secretion is a key event on which we should focus to inhibit tumorigenic and metastatic phenotype of human melanoma.…”
Section: Introductionmentioning
confidence: 97%
“…19 In vivo, cells transfected with this anti-CTSLScFv produced less and smaller tumors with a decrease of vascularization (angiogenesis) and an increase of cell apoptosis. 19 Furthermore, our recent demonstrations that overexpression of cathepsin L in human tumor cells is under the control of separate and complex regulatory mechanisms 20,21 support that procathepsin L secretion is a key event on which we should focus to inhibit tumorigenic and metastatic phenotype of human melanoma. As detailed above, our previous experiments were performed by processing human melanoma cells before their injections in nude mice, with polyclonal anti-CTSL antibodies, 8 cathepsin L cDNA 10 or anti-CTSL-ScFv.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation